2017
DOI: 10.1177/1177625017713193
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and Knockdown of Hypoxia-Inducible Factor 1 Disrupt the Expression of Steroidogenic Enzyme Genes and Early Embryonic Development in Zebrafish

Abstract: Hypoxia is an important environmental stressor leading to endocrine disruption and reproductive impairment in fish. Although the hypoxia-inducible factor 1 (HIF-1) is known to regulate the transcription of various genes mediating oxygen homeostasis, its role in modulating steroidogenesis-related gene expression remains poorly understood. In this study, the regulatory effect of HIF-1 on the expression of 9 steroidogenic enzyme genes was investigated in zebrafish embryos using a “gain-of-function and loss-of-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
2
25
0
Order By: Relevance
“…It was also reported that intermittent hypoxia (10% O 2 for 17 days) could cause abnormal synthesis of STAR protein and inhibit testosterone secretion in rats (Zhang et al 2013). In vivo studies with zebrafish also showed that upregulation of HIF1 expression could inhibit the synthesis of STAR protein (Tan et al 2017). Although these studies have proved that HIF1 represses STAR expression, the underlying molecular mechanism was not clarified.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that intermittent hypoxia (10% O 2 for 17 days) could cause abnormal synthesis of STAR protein and inhibit testosterone secretion in rats (Zhang et al 2013). In vivo studies with zebrafish also showed that upregulation of HIF1 expression could inhibit the synthesis of STAR protein (Tan et al 2017). Although these studies have proved that HIF1 represses STAR expression, the underlying molecular mechanism was not clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the role of HIFs in the regulation of steroidogenesis in vitro are few, apart from those in zebra fish larvae that describe differential regulation of the enzymes involved in the steroid pathway (7,18,20). However, to the best of our knowledge, there are no mouse models to study the role of HPPs in adrenal cortical cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies and reports on HIF1α alterations in zebrafish larvae have suggested negative regulation of StAR, the mitochondrial cholesterol transporter (7,17,20). However, data on the effects of HPP alterations in adrenal cortex of mice is scant at best.…”
Section: Loss Of Phd2/hif1α In Adrenocortical Cells Impacts Gene Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent experimental study, however, revealed that Hif-1α is also required for proper embryonic development in fish. Overexpression of hif-1α mRNA in zebrafish resulted in developmental retardation and in a significant increase in developmental defects (Tan et al, 2017). Knockdown of hif-1α using morpholinos (see Glossary) in turn resulted in morphological abnormalities such as small head circumferences, deformed hearts, curved tails and a reduced growth rate (Tan et al, 2017).…”
Section: Expression Of Hif Isoforms During Developmentmentioning
confidence: 99%